Strong friction bionic surface suitable for smooth and rough surfaces and preparation method

By using epoxy-based shape memory polymer with variable stiffness in the bionic adhesion surface, combined with inclined microcylindrical arrays and secondary microcylindrical arrays, the problem of insufficient shear resistance on rough surfaces in the prior art is solved, and the effect of showing high normal adhesion and shear resistance on both smooth and rough surfaces is achieved.

CN119613778APending Publication Date: 2025-03-14SOUTHWEST JIAOTONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411794147.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing bionic adhesion surfaces exhibit high friction on smooth surfaces, but the normal adhesion and shear resistance are greatly reduced when the surface is rough, making it difficult to have both.

Method used

Using epoxy-based shape memory polymer with variable stiffness, the structure is divided into three layers: backing layer, inclined microcylindrical array and secondary microcylindrical array. The material is converted between the rubber state and the glass state through temperature adjustment, thereby adjusting the structural stiffness and contact state and improving shear resistance.

Benefits of technology

It has achieved high normal adhesion and shear resistance on both smooth and rough surfaces, especially on surfaces with higher roughness, and has a simple preparation process, low cost, and good durability and pollution resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613778A_ABST
    Figure CN119613778A_ABST
Patent Text Reader

Abstract

The invention discloses a strong friction bionic surface suitable for smooth and rough surfaces and a preparation method, the strong friction bionic surface comprises a rigidity-variable epoxy shape memory polymer, the rigidity-variable epoxy shape memory polymer is structurally divided into three layers, namely a backing layer, an inclined micro-cylinder array and a smaller-size secondary micro-cylinder array from bottom to top, the backing layer is conveniently fixed on a heating substrate and transfers heat, and the inclined micro-cylinder array is low in rubber-state cylinder modulus in a normal contact stage, so that the inclined micro-cylinder array can be in conformal contact with a dual surface better; before sliding friction, the cylinder is switched to be in a glassy state, the modulus is high, deformation is small, the anti-shearing effect can be effectively improved, and damage caused by large deformation is not likely to happen; the second-stage micro-column array has low contact rigidity when being in contact with a smooth surface or a rough surface, can be well adapted to planes with different sizes of roughness, and is embedded with rough peaks to increase the contact area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of robots, and in particular relates to a strong friction bionic surface suitable for smooth and rough surfaces and a preparation method thereof. Background Art

[0002] In recent years, the study of flexible adhesive surfaces inspired by geckos has developed into a mature field. Geckos can climb freely on smooth and rough walls, thanks to the synergistic effect of the tiny bristles on their soles and the muscles on the soles. When the gecko's sole contacts the target surface, in addition to the van der Waals force provided by the tiny cilia, the synergistic effect of the sole muscles maintains and locks the sole shape, thereby enhancing adhesion. When contacting a smooth surface, the van der Waals force of the tiny cilia plays a crucial role in adhesion. When contacting a rough surface, the hardening and locking shape of the sole muscles increases the contact area between the sole and the surface, thereby improving adhesion. However, most of the current gecko-inspired adhesive surfaces are only suitable for smooth surfaces, and the normal adhesion and shear resistance are greatly reduced on a wide range of rough surfaces. Therefore, it is of great scientific significance and application value to develop an adhesive surface that has both high friction on smooth surfaces and high shear resistance on rough surfaces.

[0003] Murphy et al. (Murphy MP, Aksak B, Sitti M. Gecko-Inspired Directional and Controllable Adhesion [J]. Small, 2009, 5 (2): 170–175.) proposed an adhesive structure consisting of an array of tilted polyurethane microfibers with mushroom-shaped tips. The structure has a shear force of up to 100 kPa on a smooth surface and exhibits anisotropy, with a shear force that differs five times in the grasping and releasing directions. However, the adhesive surface has a high shear strength only on smooth surfaces and is not suitable for rough surfaces.

[0004] Li et al. (Li S, Tian H, Shao J, et al. Switchable Adhesion for Nonflat Surfaces Mimicking Geckos' Adhesive Structures and Toe Muscles [J]. ACS Applied Materials & Interfaces, 2020, 12 (35): 39745–39755.) proposed a layered structure that simulates the adhesion structure and toe muscles of geckos. The structure consists of a polydimethylsiloxane elastomer mushroom-shaped adhesion layer, a thermoformed polyurethane, and an electronic heating layer, which can achieve high and switchable adhesion on non-flat surfaces. The structural stiffness is adjusted by voltage to achieve active grasping and release. However, due to the soft adhesion pad on the surface, the structure has weak shear resistance on rough surfaces.

[0005] Linghu et al. (Linghu C, Liu Y, Yang X, et al. Fibrillar adhesives with unexpected adhesion strength, switchability and scalability [J]. National Science Review, 2024, 11 (10): nwae106.) proposed a fiber adhesion structure that uses the transition from the rubber state to the glass state of shape memory polymers to achieve normal adhesion. It has high normal adhesion strength, flexible switching between adhesion and desorption, and scalability, showing excellent normal adhesion performance. The bionic fiber adhesion object of this study is a smooth glass substrate, and the adhesion performance on the rough surface is not studied, nor is its shear resistance or static friction behavior on surfaces of different roughness.

[0006] At present, the adhesive surface inspired by geckos mainly achieves the adhesion effect by imitating the tiny bristle structure of the gecko's feet and using van der Waals force. The main preparation method of this type of surface is the photolithography template method, and the commonly used materials include polyurethane and polydimethylsiloxane. The main disadvantages of the existing technology include: first, the flexible adhesive material is prone to large deformation under the action of tangential contact load, and it is difficult to maintain the adhesion state; second, it is only applicable to surfaces with a roughness Sq less than ten microns. When the roughness increases further, the interfacial adhesion strength will be significantly reduced; third, the strong adhesion of the flexible adhesive material is derived from the strong intermolecular force. When the contact surface is contaminated or the surface energy is low, the strong adhesion is easy to fail.

[0007] Although existing bionic adhesion structures combined with variable stiffness materials can achieve adhesion to smooth or rough surfaces, a bionic adhesion surface with excellent shear resistance on both smooth and rough surfaces has not yet appeared. Summary of the invention

[0008] The purpose of the present invention is to solve the above problems and provide a high-friction bionic surface suitable for smooth and rough surfaces, which has a simple preparation process, low cost, and a structural size of several hundred microns, thereby ensuring structural strength, improving durability and anti-pollution ability.

[0009] In order to solve the above technical problems, the technical solution of the present invention is: a high-friction bionic surface suitable for smooth and rough surfaces, including an epoxy-based shape memory polymer with variable stiffness. The epoxy-based shape memory polymer structure with variable stiffness is divided into three layers, from bottom to top, respectively, a backing layer, an inclined micro-cylinder array and a secondary micro-cylinder array of smaller size. The backing layer is convenient for fixing on a heated substrate and transferring heat. In the normal contact stage, the inclined micro-cylinder array has a low rubber-state cylinder modulus and can better produce conformal contact with the dual surface; before sliding friction, it switches to a glass-state cylinder with a high modulus and small deformation, which can effectively increase the shear resistance and is not easily damaged by large deformation; the secondary micro-cylinder array has a lower contact stiffness when in contact with a smooth surface or a rough surface, can adapt well to roughness planes of different sizes, and fit with the rough peak to increase the contact area.

[0010] Furthermore, the epoxy shape memory polymer SMP has a low elastic modulus (about several MPa) when the temperature is higher than the glass transition temperature Tg, that is, the rubber state (RS), and a high elastic modulus (about several GPa) when the temperature is lowered below Tg, that is, the glass state (GS); secondly, when the SMP is constrained and deformed in the rubber state, when the temperature is lowered and the SMP is converted to the glass state, this deformation will be locked, therefore, after the SMP is converted from the rubber state to the glass state (R2G), a variable stiffness and shape-locking effect are produced.

[0011] Furthermore, the backing layer thickness is 1000 μm, the vertical height of the inclined microcolumns is 1200 μm, the cross-sectional radius is 250 μm, the center spacing between adjacent inclined microcolumns is 1200 μm, and they are staggered. The secondary microcolumns are 45×45×60 μm quadrangular prisms with a center spacing of 60 μm.

[0012] Furthermore, the inclined microcolumns effectively improve the shear resistance. Within a certain roughness range, as the roughness increases, the effect of the inclined microcolumns in improving the shear resistance becomes more obvious.

[0013] Furthermore, the bionic surface realizes normal adhesion and anti-shearing function on the rough object surface in the following steps:

[0014] S11. Initially, the bionic structure surface with high stiffness approaches the rough surface until some contact points appear; since the heat source is not turned on at this time, the stiffness of the bionic structure surface is very high, resulting in a limited contact area between the secondary micro-column structure and the rough object surface;

[0015] S12, then turning on the heat source to increase the temperature of the bionic surface, at which time its state changes from hard to soft in a low-rigidity state, and under the action of the preload, the secondary micro-column structure fits tightly with the surface of the rough object;

[0016] S13, finally turning off the heat source, the temperature of the bionic surface drops, its state changes from soft to hard, and the close contact state is locked;

[0017] S14, when the object reaches the predetermined position, the heat source is turned on again, and the bionic surface changes from hard to soft again, and returns to the initial state under the action of the shape memory effect;

[0018] S15, cracks are then caused at the contact interface, and the object can fall off the bionic surface;

[0019] S16. Since the stiffness of the inclined microcolumn is relatively high at this time, the possibility of cracks on the contact interface is reduced; at the same time, the inclination direction of the microcolumn is consistent with the direction of the applied shear load, which will cause the friction force generated at the contact interface to have a strong antagonistic effect with the applied shear load;

[0020] S17. When the heat source is turned on again, the bionic surface changes from hard to soft and returns to a low stiffness state. At this time, cracks appear on the contact interface. At the same time, due to the softening of the inclined micro-pillars, the antagonistic effect will be greatly reduced, causing its shear strength to decrease accordingly.

[0021] The present invention also provides a method for preparing a strong friction bionic surface suitable for smooth and rough surfaces, comprising the following steps:

[0022] S21. Preparation of secondary microcolumns in resin positive mold: Use a femtosecond laser processing system to process the secondary microcolumn array on the top of the oriented microcolumns in the high-precision 3D printed resin mold, place the processed mold in anhydrous ethanol for ultrasonic cleaning for 10 minutes, and dry it for use;

[0023] S22, chemical modification: 200 μL of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane (PFDS) was dissolved in 25 mL of anhydrous ethanol, and magnetically stirred for 30 min to prepare a modification solution; the 3D printed inclined microcolumn array positive mold was immersed in the modification solution and placed in a 50°C oven for 2 h; after taking it out, it was ultrasonically cleaned in anhydrous ethanol for 10 min to remove excess PFDS, and then placed in an 80°C drying oven for 1 h to promote the complete grafting of PFDS to the surface of the positive mold;

[0024] S23, preparation of bionic surface negative mold: A and B components of silicone rubber MoldStar30 were mixed in a volume ratio of 1:1, stirred evenly with a glass rod, and poured into the bionic surface positive mold, and degassed in a vacuum drying oven for 5 minutes; then, a smooth glass sheet was covered on the positive mold, and the excess silicone rubber mixture was squeezed out. The entire positive mold was placed in an environment of 23°C for curing for 6 hours, and then demolded for use;

[0025] S24. Bionic surface replication: At room temperature, 4 g and 2.2 g of epoxy resin E44 / curing agent polyetheramine D-230 were weighed and mixed in a mass ratio of 20:11, respectively, and magnetically stirred at 60°C for 3 min, and then placed in a vacuum drying oven for degassing for 5 min; the mixed solution was poured into the inclined microcolumn array negative mold, and vacuum degassed again for 5 min to allow the mixed solution to fully fill the negative mold cavity, and a smooth glass sheet was covered on the negative mold to squeeze out excess mixed solution; then, pre-cured in a drying oven at 100°C for 1 h, and then cured at 130°C for another 1 h, and demolded for use.

[0026] Furthermore, in S21, the femtosecond laser processing system processes the secondary microcolumn array by setting processing parameters such as laser power, frequency, energy, scanning path, number of scans and scanning speed, and performs laser processing according to the processing pattern route to obtain a bionic surface positive mold.

[0027] Furthermore, after the positive mold in S22 is modified by PFDS, the surface energy of the positive mold is reduced, which is conducive to the complete replication of the bionic surface negative mold.

[0028] The beneficial effects of the present invention are:

[0029] 1. The high friction bionic surface and preparation method suitable for smooth and rough surfaces provided by the present invention are of great significance for the high normal adhesion and shear-resistant controllable variable stiffness bionic surface that can actively adjust its own structural stiffness and contact state according to the roughness of the contact surface.

[0030] 2. The present invention can adjust the contact state according to the roughness of the contact surface, and achieve high normal adhesion and shear resistance on surfaces with different roughness, especially suitable for surfaces with a roughness of tens of microns or more. In addition, the preparation process of the bionic surface is simple and low-cost, and the structural size of several hundred microns can ensure the structural strength, improve durability and anti-pollution ability.

[0031] 3. The present invention learns from nature. In the natural environment, geckos need to play an adhesion and desorption role on target surfaces with different roughness. Its mechanism of action does not only rely on the strong adhesion of bristles. For example, when the roughness increases, geckos use the hardening and locking effect of the sole muscles to evenly disperse the stress on the entire sole under the shear load, so that the shear deformation of the contact surface is reduced, and the sudden drop trend of the contact area between the sole and the surface under the shear action is suppressed, thereby improving the adhesion on the rough surface. Inspired by this, the present invention proposes a strong friction bionic surface design and preparation method suitable for smooth and rough surfaces. Based on the synergistic effect of the variable stiffness oriented micro-column array structure and the surface microstructure layer on the top of the micro-column, a stable normal adhesion force can be generated on both smooth and wide-range roughness surfaces, and under the action of shear force, it has a higher static friction, that is, the ability to resist shear loads, and has the characteristics of simple preparation and low cost. This provides a new solution for the surface design of the end effector of flexible grasping and climbing robots.

[0032] 4. The bionic variable stiffness controllable adhesion surface of the present invention is inspired by geckos and can exhibit excellent adhesion and shear resistance on both smooth and large-scale rough surfaces. When the bionic surface in a low stiffness state contacts with planes of different roughness, the secondary microcolumns can contact the plane or rough peak well, increasing the contact area. Subsequently, the bionic surface changes from a low stiffness state to a high stiffness state, the state of the contact interface is locked, and the contact stress is evenly distributed on the contact interface, greatly reducing the possibility of crack propagation, thereby improving the adhesion ability, and at the same time, the tilted microcolumns effectively improve the shear resistance of the bionic surface on the rough plane. In addition, since the method of the present invention does not strongly rely on intermolecular forces, it relies on variable stiffness and locking effects to avoid debonding failure caused by decreased intermolecular forces. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the composition of a strong friction bionic surface structure suitable for smooth and rough surfaces of the present invention;

[0034] Figure 2 It is a schematic diagram of the adhesion and anti-shear principle of the present invention;

[0035] Figure 3 is a flow chart for preparing the bionic adhesion surface of the present invention;

[0036] Figure 4 It is a graph showing the normal adhesion test results of the present invention with different sizes of preloads and smooth glass and 1000# sandpaper replica surface;

[0037] Figure 5 This is a graph showing the tangential friction test results of the present invention with different sizes of preloads and smooth glass and 1000# sandpaper replica surfaces;

[0038] Figure 6 The graph is a result of normal adhesion and tangential friction test on smooth glass, rough glass, 3000#, 1000#, 180#, and 80# sandpaper replica surfaces by applying preloads of different sizes in the present invention. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments:

[0040] like Figures 1 to 6 As shown, the present invention provides a high-friction bionic surface suitable for smooth and rough surfaces, including an epoxy-based shape memory polymer with variable stiffness. The epoxy-based shape memory polymer with variable stiffness has a three-layer structure, which includes, from bottom to top, a backing layer, an inclined micro-cylinder array, and a secondary micro-cylinder array of smaller size. The backing layer is convenient for fixing on a heated substrate and transferring heat. In the normal contact stage, the inclined micro-cylinder array has a low rubber-state cylinder modulus and can better produce conformal contact with the dual surface; before sliding friction, it switches to a glass-state cylinder with a high modulus and small deformation, which can effectively increase the shear resistance and is not easily damaged by large deformation; the secondary micro-cylinder array has a lower contact stiffness when in contact with a smooth surface or a rough surface, can adapt well to roughness planes of different sizes, and fits with the rough peak to increase the contact area.

[0041] When the temperature of epoxy shape memory polymer SMP is higher than the glass transition temperature Tg, that is, the rubber state (RS), its elastic modulus is low (about several MPa), and when the temperature is lower than Tg, that is, the glass state (GS), its elastic modulus is higher (about several GPa). Secondly, when SMP is constrained and deformed in the rubber state, when the temperature is lowered and SMP is converted to the glass state, this deformation will be locked. Therefore, after SMP is converted from the rubber state to the glass state (R2G), variable stiffness and locking effect are produced.

[0042] The thickness of the backing layer is 1000 μm, the vertical height of the inclined microcolumns is 1200 μm, the cross-sectional radius is 250 μm, the center spacing between adjacent inclined microcolumns is 1200 μm, and they are staggered. The secondary microcolumns are 45×45×60 μm quadrangular prisms with a center spacing of 60 μm.

[0043] The inclined microcolumns can effectively improve the shear resistance. Within a certain range of roughness, as the roughness increases, the effect of the inclined microcolumns in improving the shear resistance becomes more obvious.

[0044] The backing layer is easy to fix on the heating substrate and transfer heat. The inclined micro-cylinder array effectively increases the shear resistance during unidirectional sliding and is not easily damaged by large deformation. The secondary micro-cylinder array has a lower contact stiffness when in contact with a smooth surface or a rough surface, and can adapt well to roughness planes of different sizes and fit with the rough peaks to increase the contact area.

[0045] The steps of the bionic surface to achieve normal adhesion and anti-shear function on the rough surface are as follows:

[0046] S11. Initially, the bionic structure surface with high stiffness approaches the rough surface until some contact points appear; since the heat source is not turned on at this time, the stiffness of the bionic structure surface is very high, resulting in a limited contact area between the secondary microcolumn structure and the rough object surface.

[0047] S12. Then, the heat source is turned on to increase the temperature of the bionic surface. At this time, its state changes from hard to soft and is in a low stiffness state. Under the action of the preload, the secondary micro-column structure fits tightly with the surface of the rough object.

[0048] S13. Finally, turn off the heat source, the temperature of the bionic surface drops, and its state changes from soft to hard, and the close contact state is locked. Figure 2 As shown in state III in (a), corresponding to the normal adhesion function, the purpose of picking up objects can be achieved while reducing the possibility of crack propagation at the contact interface.

[0049] S14, when the object reaches the predetermined position, the heat source is turned on again, and the bionic surface changes from hard to soft again, and under the action of the shape memory effect, returns to the initial state. Figure 2 As shown in (a)Ⅳ.

[0050] S15. Subsequently, cracks are caused at the contact interface and the object can fall off the bionic surface.

[0051] like Figure 2 (b) Ⅲ corresponds to the friction-increasing function, which can achieve the purpose of enhancing the shear resistance. Figure 2 (a) is a schematic diagram of the principle of the bionic structure surface realizing the normal adhesion function on the surface of a rough object, and (b) is a schematic diagram of the principle of the bionic structure surface realizing the anti-shear function on the surface of a rough object.

[0052] S16. Since the stiffness of the inclined microcolumn is relatively high at this time, the possibility of cracks forming at the contact interface is reduced; at the same time, the inclination direction of the microcolumn is consistent with the direction of the applied shear load, which will cause the friction force generated at the contact interface to have a strong antagonistic effect with the applied shear load.

[0053] S17. When the heat source is turned on again, the bionic surface changes from hard to soft and returns to a low stiffness state. At this time, cracks appear on the contact interface. At the same time, due to the softening of the tilted micro-pillars, the antagonistic effect is greatly reduced, resulting in a decrease in its shear strength. Figure 2 As shown in (b)Ⅳ.

[0054] The present invention also discloses a method for preparing a strong friction bionic surface suitable for smooth and rough surfaces, comprising the following steps:

[0055] S21. Preparation of secondary microcolumns in resin positive mold: Use a femtosecond laser processing system to process the secondary microcolumn array on the top of the oriented microcolumn of the high-precision 3D printed resin mold, place the processed mold in anhydrous ethanol for ultrasonic cleaning for 10 minutes, and dry it for use.

[0056] In step S21, the femtosecond laser processing system processes the secondary microcolumn array by setting processing parameters such as laser power, frequency, energy, scanning path, scanning times and scanning speed according to the processing pattern route to obtain a bionic surface positive mold.

[0057] S22. Chemical modification: 200 μL of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane (PFDS) was dissolved in 25 mL of anhydrous ethanol and magnetically stirred for 30 min to prepare a modification solution; the 3D printed inclined microcolumn array positive mold was immersed in the modification solution and placed in a 50°C oven for 2 h; after taking it out, it was ultrasonically cleaned in anhydrous ethanol for 10 min to remove excess PFDS, and then placed in an 80°C drying oven for 1 h to promote the complete grafting of PFDS to the surface of the positive mold.

[0058] After the positive mold is modified by PFDS, the surface energy of the positive mold is reduced, which is conducive to the complete replication of the negative mold of the bionic surface.

[0059] S23. Preparation of bionic surface negative mold: Mix the A and B components of silicone rubber MoldStar30 in a volume ratio of 1:1, stir evenly with a glass rod, and pour into the bionic surface positive mold. Degas in a vacuum drying oven for 5 minutes. Then, cover the positive mold with a smooth glass sheet, squeeze out the excess silicone rubber mixture, and place the entire positive mold at 23°C for curing for 6 hours, then demold and set aside.

[0060] S24. Bionic surface replication: At room temperature, 4 g and 2.2 g of epoxy resin E44 / curing agent polyetheramine D-230 were weighed and mixed in a mass ratio of 20:11, respectively, and magnetically stirred at 60°C for 3 min, and then placed in a vacuum drying oven for degassing for 5 min; the mixed solution was poured into the inclined microcolumn array negative mold, and vacuum degassed again for 5 min to allow the mixed solution to fully fill the negative mold cavity, and a smooth glass sheet was covered on the negative mold to squeeze out excess mixed solution; then, pre-cured in a drying oven at 100°C for 1 h, and then cured at 130°C for another 1 h, and demolded for use.

[0061] The bionic surface was subjected to normal adhesion tests with smooth glass and 1000# sandpaper replica surfaces under different preloads in glassy state (GS), rubbery state (RS) and rubber-to-glass state (R2G). The test results are shown in Figure 2. Figure 4 shown. Figure 4(a) is the preload result diagram of normal adhesion test on smooth glass with preloads of different sizes, and (b) is the result diagram of normal adhesion test on 1000# sandpaper replica surface with preloads of different sizes.

[0062] The bionic surface was subjected to tangential friction tests with smooth glass and 1000# sandpaper replica surfaces under different preloads in glass state (GS), rubber state (RS) and rubber-to-glass state (R2G). The test results are shown in Figure 2. Figure 5 shown. Figure 5 (a) shows the results of tangential friction tests on smooth glass with different preloads, and (b) shows the results of tangential friction tests on a replica surface of 1000# sandpaper with different preloads.

[0063] When the bionic surface was converted from rubber to glass (R2G), normal adhesion and tangential friction tests were performed on smooth glass, rough glass, and 3000#, 1000#, 180#, and 80# sandpaper replicas by applying different preloads. The test results are shown in Figure 2. Figure 6 shown. Figure 6 (a) shows the normal adhesion test results of smooth glass, rough glass, 3000#, 1000#, 180#, and 80# sandpaper replica surfaces with different preloads, and (b) shows the tangential friction test results of smooth glass, rough glass, 3000#, 1000#, 180#, and 80# sandpaper replica surfaces with different preloads.

[0064] The present invention utilizes the variable stiffness characteristics and shape locking effect of shape memory polymers during the transition process between rubber and glass states to design and prepare a bionic surface with high normal adhesion and strong friction capabilities, which has the following characteristics:

[0065] 1. Excellent normal adhesion and shear resistance: The bionic surface has excellent normal adhesion and shear resistance on both smooth and rough surfaces, which broadens the scope of application.

[0066] 2. Switchable normal adhesion and tangential friction: The bionic surface has high normal adhesion and high shear resistance in the R2G state, and low normal adhesion and low shear resistance in the rubber state, which facilitates the grasping and releasing of objects.

[0067] 3. High shear resistance on rough surfaces: When the adhesive structure contacts the rough surface, it can reduce its own structural stiffness and switch the contact state. The secondary micro-pillars are embedded with the rough peaks, and then restore high stiffness and lock the shape, thereby achieving shear resistance.

[0068] 4. Inclined micro-columns effectively improve shear resistance: Within a certain roughness range, as the roughness increases, the effect of inclined micro-columns in improving shear resistance becomes more obvious.

[0069] 5. Excellent mechanical properties: When the inclined microcolumns encounter high shear force, they will fall in the direction of the shear force and are not easily damaged by large deformation.

[0070] 6. Structural size scalability: The structural size of the inclined microcolumns and secondary microcolumns can be further reduced or increased, and they also have normal adhesion and anti-shear effects, and the adaptability range of the optimal roughness also decreases or increases accordingly.

[0071] Those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.

Claims

1. A high friction bionic surface suitable for smooth and rough surfaces, characterized by: It includes an epoxy-based shape memory polymer with variable stiffness. The structure of the epoxy-based shape memory polymer with variable stiffness is divided into three layers, from bottom to top, namely a backing layer, an inclined micro-cylinder array and a smaller secondary micro-cylinder array. The backing layer is convenient for fixing on a heated substrate and transferring heat. In the normal contact stage, the inclined micro-cylinder array has a low rubber-state cylinder modulus and can better produce conformal contact with the dual surface; before sliding friction, it switches to a glass-state cylinder with a high modulus and small deformation, which can effectively increase the shear resistance and is not easily damaged by large deformation; the secondary micro-cylinder array has a lower contact stiffness when in contact with a smooth surface or a rough surface, can adapt well to roughness planes of different sizes, and fits with the rough peaks to increase the contact area.

2. The high friction bionic surface suitable for smooth and rough surfaces according to claim 1, characterized in that: The epoxy-based shape memory polymer SMP has a low elastic modulus (about several MPa) when the temperature is higher than the glass transition temperature Tg, that is, the rubber state (RS), and a high elastic modulus (about several GPa) when the temperature is lowered below Tg, that is, the glass state (GS); secondly, when the SMP is constrained and deformed in the rubber state, when the temperature is lowered and the SMP is converted to the glass state, this deformation will be locked, therefore, after the SMP is converted from the rubber state to the glass state (R2G), a variable stiffness and locking effect are produced.

3. The high friction bionic surface suitable for smooth and rough surfaces according to claim 1, characterized in that: The backing layer thickness is 1000 μm, the vertical height of the inclined microcolumns is 1200 μm, the cross-sectional radius is 250 μm, the center spacing between adjacent inclined microcolumns is 1200 μm, and they are staggered. The secondary microcolumns are 45×45×60 μm quadrangular prisms with a center spacing of 60 μm.

4. The high friction bionic surface suitable for smooth and rough surfaces according to claim 1, characterized in that: The inclined microcolumns effectively improve the shear resistance. Within a certain roughness range, as the roughness increases, the effect of the inclined microcolumns in improving the shear resistance becomes more obvious.

5. The high friction bionic surface suitable for smooth and rough surfaces according to claim 1, characterized in that: The steps of the bionic surface realizing normal adhesion and anti-shearing function on the rough object surface are as follows: S11. Initially, the bionic structure surface with high stiffness approaches the rough surface until some contact points appear; since the heat source is not turned on at this time, the stiffness of the bionic structure surface is very high, resulting in a limited contact area between the secondary micro-column structure and the rough object surface; S12, then turning on the heat source to increase the temperature of the bionic surface, at which time its state changes from hard to soft in a low-rigidity state, and under the action of the preload, the secondary micro-column structure fits tightly with the surface of the rough object; S13, finally turning off the heat source, the temperature of the bionic surface drops, its state changes from soft to hard, and the close contact state is locked; S14, when the object reaches the predetermined position, the heat source is turned on again, and the bionic surface changes from hard to soft again, and returns to the initial state under the action of the shape memory effect; S15, cracks are then caused at the contact interface, and the object can fall off the bionic surface; S16. Since the stiffness of the inclined microcolumn is relatively high at this time, the possibility of cracks on the contact interface is reduced; at the same time, the inclination direction of the microcolumn is consistent with the direction of the applied shear load, which will cause the friction force generated at the contact interface to have a strong antagonistic effect with the applied shear load; S17. When the heat source is turned on again, the bionic surface changes from hard to soft and returns to a low stiffness state. At this time, cracks appear on the contact interface. At the same time, due to the softening of the inclined micro-pillars, the antagonistic effect will be greatly reduced, causing its shear strength to decrease accordingly.

6. The high friction bionic surface suitable for smooth and rough surfaces according to claim 1, characterized in that: The method for preparing a strong friction bionic surface suitable for smooth and rough surfaces comprises the following steps: S21. Preparation of secondary microcolumns in resin positive mold: Use a femtosecond laser processing system to process the secondary microcolumn array on the top of the oriented microcolumns in the high-precision 3D printed resin mold, place the processed mold in anhydrous ethanol for ultrasonic cleaning for 10 minutes, and dry it for use; S22, chemical modification: 200 μL of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane (PFDS) was dissolved in 25 mL of anhydrous ethanol, and magnetically stirred for 30 min to prepare a modification solution; the 3D printed inclined microcolumn array positive mold was immersed in the modification solution and placed in a 50°C oven for 2 h; after taking it out, it was ultrasonically cleaned in anhydrous ethanol for 10 min to remove excess PFDS, and then placed in an 80°C drying oven for 1 h to promote the complete grafting of PFDS to the surface of the positive mold; S23, preparation of bionic surface negative mold: A and B components of silicone rubber MoldStar30 were mixed in a volume ratio of 1:1, stirred evenly with a glass rod, and poured into the bionic surface positive mold, and degassed in a vacuum drying oven for 5 minutes; then, a smooth glass sheet was covered on the positive mold, and the excess silicone rubber mixture was squeezed out. The entire positive mold was placed in an environment of 23°C for curing for 6 hours, and then demolded for use; S24. Bionic surface replication: At room temperature, 4 g and 2.2 g of epoxy resin E44 / curing agent polyetheramine D-230 were weighed and mixed in a mass ratio of 20:11, respectively, and magnetically stirred at 60°C for 3 min, and then placed in a vacuum drying oven for degassing for 5 min; the mixed solution was poured into the inclined microcolumn array negative mold, and vacuum degassed again for 5 min to allow the mixed solution to fully fill the negative mold cavity, and a smooth glass sheet was covered on the negative mold to squeeze out excess mixed solution; then, pre-cured in a drying oven at 100°C for 1 h, and then cured at 130°C for another 1 h, and demolded for use.

7. The high friction bionic surface suitable for smooth and rough surfaces according to claim 1, characterized in that: In S21, the femtosecond laser processing system processes the secondary microcolumn array by setting processing parameters such as laser power, frequency, energy, scanning path, number of scans and scanning speed, and laser processing is performed according to the processing pattern route to obtain a bionic surface positive mold.

8. The high friction bionic surface suitable for smooth and rough surfaces according to claim 1, characterized in that: After the positive mold in S22 is modified by PFDS, the surface energy of the positive mold is reduced, which is conducive to the complete replication of the bionic surface negative mold.

Citation Information

Cited By

  • Design and preparation method for variable-stiffness surface of insect-imitating foot pad with strong friction characteristic

    CN120156170A

  • Bionic friction pad, preparation method thereof and clamp comprising bionic friction pad

    CN121716104A